2000
DOI: 10.1128/jb.182.15.4198-4206.2000
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution and Partial Characterization of Phospholipid Flippase Activity from Detergent Extracts of the Bacillus subtilis Cell Membrane

Abstract: In bacteria, phospholipids are synthesized on the inner leaflet of the cytoplasmic membrane and must translocate to the outer leaflet to propagate a bilayer. Transbilayer movement of phospholipids has been shown to be fast and independent of metabolic energy, and it is predicted to be facilitated by membrane proteins (flippases) since transport across protein-free membranes is negligible. However, it remains unclear as to whether proteins are required at all and, if so, whether specific proteins are needed. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 45 publications
9
56
0
Order By: Relevance
“…2, trace a). Time-dependent fluorescence quenching of liposomes follows single phase exponential decay kinetics as reported earlier [10]. Liposomes when reconstituted with ePC and lipids extracted from bovine liver ER and spinach leaf ER showed no flippase activity ( Fig.…”
Section: Flippase Activity Measurement By Dithionite Reductionsupporting
confidence: 76%
See 1 more Smart Citation
“…2, trace a). Time-dependent fluorescence quenching of liposomes follows single phase exponential decay kinetics as reported earlier [10]. Liposomes when reconstituted with ePC and lipids extracted from bovine liver ER and spinach leaf ER showed no flippase activity ( Fig.…”
Section: Flippase Activity Measurement By Dithionite Reductionsupporting
confidence: 76%
“…However, biogenic or self-synthesizing membranes are equipped with a special class of protein translocators called biogenic membrane flippases, which are involved in rapid flip-flop of PLs (irrespective of PL head group) and are metabolic energy independent, thereby differing from conventional ATP-dependent flippases which are localized at non-biogenic membranes such as plasma membrane (PM) [9]. Biogenic membrane flippase activity has been shown in bacterial cytoplasmic membranes, and ER of animals and plants [10][11][12]. We hypothesize that cholesterol affects the rapid flip-flop of PLs across the bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments designed to study phospholipid flip-flop in bacterial membranes and model liposomes have suggested that this process might be energy-independent in bacteria (58,59). In model membranes, lipid flip-flop occurs at near physiological rates in the absence of ATP or a proton motive force, provided that synthetic membrane-spanning peptides are reconstituted together with the lipids (60).…”
Section: Discussionmentioning
confidence: 99%
“…The present study makes use of a detergent-based vesicle reconstitution protocol in which Triton X-100-solubilized phospholipids and ER membrane proteins are incubated with detergent-adsorbing Bio-Beads. Although greater than 99% of the detergent is removed during this procedure (26) to generate large unilamellar vesicles, we considered whether residual detergent in the vesicles could affect the spontaneous flip-flop of lipids.…”
Section: Spontaneous Flipping Of Nbd-labeled Lipids Is Slow In Vesiclesmentioning
confidence: 99%